Pembelajaran PAI untuk Menumbuhkan Etika Pemanfaatan Energi dan Sumber Daya Alam - Nurul Fajar; Muslichah Muslichah; Dimas Junior (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Environmental awareness is a crucial aspect in developing students' character in the modern era, particularly in the face of global challenges such as climate change, environmental damage, and natural resource degradation. Islamic Religious Education (PAI) holds significant potential in contributing to increasing students' environmental awareness through the integration of spiritual values ​​and contextual learning practices. This study aims to analyze the role of PAI in increasing students' environmental awareness through a literature review of various recent scientific sources. The research method used is a descriptive literature review approach, which examines theories, research findings, and practices of integrating Islamic values ​​into environmental education. The study's findings indicate that Islamic teachings, such as the concept of caliph (leader), amanah (responsibility), the prohibition on destroying the earth, and the recommendation to maintain cleanliness and preserve nature, play a significant role in shaping students' ecological behavior. Furthermore, the application of project-based learning methods, value-based learning, and reflective learning models have been shown to help students connect religious teachings with concrete actions in environmental protection. Thus, Islamic Religious Education (PAI) not only teaches ritual aspects, but also plays a strategic role in building ecological awareness as part of the implementation of faith, morals, and social responsibility.